Divine order and secular social science in Alexis de Tocqueville's Democracy in America - Handler, Richard (Religion, 2021)
Alexis de Tocqueville’s Democracy in America can be read as an extended anthropological comparison of hierarchical and egalitarian societies (‘aristocracies’ and ‘democracies,’ in his terms). In its use of comparative method, it is strikingly modern, almost post-modern: secular social science. And yet, for Tocqueville, divine knowledge provided another comparative perspective. In this essay, I explore the implications of Tocqueville’s consideration of divine order for his work as a seemingly secular comparative anthropologist. I argue that one of the foundational concepts of secular social science, ‘society,’ may not be universally applicable since, as Tocqueville’s work suggests, it is ill-suited for the study of people who thought of their world as a divine, not a social, order.